Fixed Costs and the Product Market Treatment of Preference Minorities1. (22nd September 2016) - Berry, Steven; Eizenberg, Alon; Waldfogel, Joel
Abstract : We clarify the sense in which the market outcome may be biased against preference minorities, and estimate the degree of bias using an empirical model of entry into American radio broadcasting markets. Listening model estimates are used to infer fixed costs, and these estimates are then used to compute optimal station configurations as well as the welfare weights on different groups that rationalize the observed configuration. Welfare weights are 2 to 3 times higher for whites than for blacks, and 1.5 to 2 times higher for non‐Hispanic than for Hispanic, listeners. We explore the role of 'importing' and 'exporting' patterns in generating these findings.